The Cross-Sectional Study on The Relationship Between The Risk Factors For High Blood Pressure of Samarinda Health Quarantine's Employees - Parengkuan, Sandra; Pakki, Irfansyah Baharudin; Wisnuwardani, Ratih Wirapuspita (An Idea Health Journal, 2025)
Background: Hypertension is the leading cause of mortality worldwide, with 90– 95% of cases classified as essential hypertension. According to data on noncommunicable or degenerative diseases in East Kalimantan, 595,689 individuals over the age of 15 were projected to suffer from hypertension in 2023. Several factors contribute to the prevalence of hypertension in Indonesia, including age, sex, family history of hypertension, educational level, occupation, place of residence, nutrition and lifestyle, and physical activity. The aim of this study was to examine the association between individual characteristics and nutritional status with the risk of hypertension among employees of the Class I Health Quarantine Office (Balai Karantina Kesehatan/BKK) in Samarinda, aged between 27 and 57 yearsMethods: This research employed a cross-sectional design involving 47 civil servants, comprising both permanent (PNS) and contract-based (PPPK) staff. Blood pressure and nutritional status (body mass index) data were obtained through direct measurements conducted in March 2025 at the BKK Class I Samarinda Office.The findings of this study indicate a significant association between individual characteristics specifically age and nutritional status and the incidence of hypertension among the employees.